HISTORISITAS PERIWAYATAN DAN KODIFIKASI HADIS: DINAMIKA TRANSMISI, OTORITAS, DAN KANONISASI SUNNAH DALAM ISLAM AWAL - Ainun Jariah; Muhammad Yahya (Ikatan Sarjana Al-Qur'an Indonesia (ISQI), 2026)
This article aims to analyze the historicity of hadith transmission and codification and explain the dynamics of transmission, the formation of authority, and the canonization process of the Sunnah in early Islam. This study is motivated by academic debates regarding the authenticity of hadith, the development of transmission traditions, and the construction of religious authority in Islamic intellectual history. This research is a library research with a historical-critical approach and historiography of hadith. Data were obtained from primary sources in the form of hadith books, works of classical scholars in the field of 'ulūm al-ḥadīṡ, as well as secondary sources in the form of books, scientific articles, and relevant contemporary research. The data were analyzed using content analysis and historical-comparative analysis techniques to comprehensively reconstruct the development of hadith transmission and codification. The results of this study indicate that the transmission of hadith in the early Islamic period developed through a dynamic interaction between oral and written traditions. The processes of transmission, verification of the sanad (chain of transmission), and codification of hadith contributed significantly to establishing the authority of the Sunnah as a source of Islamic teachings. Furthermore, the canonization of hadith served as a crucial mechanism for establishing the legitimacy of hadith collections and strengthening their position within the classical Islamic scholarly tradition. This research highlights the importance of understanding hadith as a product of knowledge transmission constructed through complex historical, methodological, and institutional processes, thus enriching the perspective of contemporary hadith studies.